Investigations into the failure mechanisms of coal bursts based on a real burst event in the Tangshan coal mine - Jia, Dongxu; Zhi, Zengzhu; Cao, Chen; Zhang, Ming (Frontiers in Earth Science, 2023)
In order to investigate the failure mechanism of coal burst in longwalls in underground coal mines, a case study based on the real coal burst in Tangshan coal mine on August 2 was carried out to analyze the cause and basic theories of coal burst, and thus propose approaches and methods to mitigate the damage. It was found that the coal burst was mainly due to the sliding of coal from the longwall ribs and the simultaneous uplift of the floor. As a result of the longwall retraction, the roof above the coal seam is too stable to collapse, forming a long hanging roof behind the longwall. Because the longwall acts as a fulcrum, the hanging roof acts like a saw, exerting massive loads on the longwall. As a result, the roof in front of the longwall would tend to slope upward, leaving the underlying coal seam unconfined. Due to the horizontal stresses in place, the longwall ribs collapse into the longwall, causing the coal seam to break out. These findings could help improve the fundamental understanding of the failure mechanisms of coal breakout and thus aid in the development of measures to prevent such occurrences.